Antifouling: Vapor‐Based Multicomponent Coatings for Antifouling and Biofunctional Synergic Modifications (Adv. Funct. Mater. 16/2014). (April 2014) - Tsai, Meng‐Yu; Chen, Yung‐Chih; Lin, Ting‐Ju; Hsu, Yin‐Chu; Lin, Ching‐Yu; Yuan, Ruei‐Hung; Yu, Jiashing; Teng, Ming‐Sheng; Hirtz, Michael; Chen, Mark Hung‐Chih; Chang, Chih‐Hao; Chen, Hsien‐Yeh
<x xml:space="preserve">Abstract</x> C.‐H. Chang, H.‐Y. Chen, and co‐workers use a direct synthesis to create a multicomponent coating containing two functionalities, achieved via CVD copolymerization on various substrates. The resulting multifunctional surface can simultaneously perform specific bioorthogonal reactions, including the azidealkyne click reaction and a thiol‐maleimide coupling reaction. This advanced surface can avoid fouling, allowing the installed groups to perform specific biofunctions with the high efficacy and accuracy necessary for delivering cascading and spontaneous biological activities. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>